2017
DOI: 10.1002/chem.201704534
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Iododeboronation with and without Gold Catalysis: Application to Radiolabelling of Arenes

Abstract: Radiopharmaceuticals that incorporate radioactive iodine in combination with single‐photon emission computed tomography imaging play a key role in nuclear medicine, with applications in drug development and disease diagnosis. Despite this importance, there are relatively few general methods for the incorporation of radioiodine into small molecules. This work reports a rapid air‐ and moisture‐stable ipso‐iododeboronation procedure that uses NIS in the non‐toxic, green solvent dimethyl carbonate. The fast reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…The RCYs of 6b obtained using our catalytic approach rival those in previous reports, outlined in Figure 1, which require reaction temperatures of 100 °C or greater, 30, 31 or 2 to 4 hour reaction times. 32, 33 Although the astatinated analogue of 6b has been disclosed by Reiner and co-workers 34 (no RCY reported), they reported a three-hour synthetic procedure with 211 At, an unusual approach considering the 7.2 hour half-life of the radionuclide.…”
supporting
confidence: 74%
“…The RCYs of 6b obtained using our catalytic approach rival those in previous reports, outlined in Figure 1, which require reaction temperatures of 100 °C or greater, 30, 31 or 2 to 4 hour reaction times. 32, 33 Although the astatinated analogue of 6b has been disclosed by Reiner and co-workers 34 (no RCY reported), they reported a three-hour synthetic procedure with 211 At, an unusual approach considering the 7.2 hour half-life of the radionuclide.…”
supporting
confidence: 74%
“…This hypothesis is supported by previous studies having reported on the radioiodination of aryltrifluoroborate or arylboronic acid precursor using electrophilic radioiodide, in the presence or absence of a catalyst. 34,35 We then probed the possibility to reduce the precursor concentration to a level acceptable for mAb radiolabelling. No drop in RCYs was observed when precursor concentration was decrease to 250 μM, a condition being chosen as it corresponds approximately, in terms of available arylboronic groups, to a solution of mAb concentrated at 6 mg mL −1 with a ratio of 6 arylboronic acids grafted per mAb.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is supported by previous studies having reported on the radioiodination of aryltrifluoroborate or arylboronic acid precursor using electrophilic radioiodide, in the presence or absence of a catalyst. 34,35 . We then probed the possibility to reduce the precursor concentration to a level acceptable for mAb radiolabelling.…”
Section: Preliminary Investigation With Model Compoundmentioning
confidence: 99%
“…Similarly, arylboronate were reported as interesting agents for radioiodination (Kabalka et al, 2002). Arylboron radioiodination chemistry was more recently revisited and improved using either base catalysis (Molloy et al, 2019), or gold catalysis (Webster et al, 2018), providing improved RCYs with otherwise less reactive (electron deficient or sterically hindered) arylboronic acid precursors. Alternately to the preparation of these above mentioned organometallic precursors, a palladium(II) mediated radioiodination approach under mild conditions was recently developed.…”
Section: I41 -Electrophilic Approachesmentioning
confidence: 99%